Strategi Pengembangan Gua Batu Cermin Labuan Bajo Sebagai Daya Tarik Wisata Alam - Enny Mulyantari; Sahlit Sugesti; Rikardus Yardiputra (STIE Pariwisata API Yogyakarta, 2024)
Mirror Stone Cave has a potential attraction that needs to be developed as a natural tourist destination, however there are several factors that are obstacles in developing the cave's attraction. Therefore, this research aims to determine the development strategy in Mirror Stone Cave in increasing the attractiveness of natural tourist destinations. The research method uses a qualitative descriptive approach. The sampling technique uses a sampling technique. Data collection is carried out by means of observation, interviews and documentation. Test the validity of the data using source and method triagulation techniques. The data obtained was analyzed using the SWOT analysis technique. The research results show that to increase attractiveness, managers need to utilize better support and cooperation with the government, surrounding communities and stakeholders. By collaborating, efforts to increase the attractiveness of Mirror Stone Cave in terms of nature conservation, promotion, infrastructure, increasing workforce, community training as well as attractions, accessibility and amenities can be optimized well.